GIFTED STUDENTS ABOUT EFFECTIVE SCHOOL PRACTICES: LESSONS LEARNED FROM EMERGENCY REMOTE EDUCATION - Krnjaić, Zora; Simic, Natasa (Studies in Teaching and Education, 2025)
This study investigates the educational experiences and perspectives of gifted students in Serbia during emergency remote education (ERE). Gifted students were selected based on recommendations from school counselors due to their exceptional abilities and achievements. The sample included 19 students from elementary schools and 11 from secondary schools, purposefully chosen to ensure homogeneity. Through semi-structured interviews, the research explores various aspects of students' lives during the pandemic, but in this paper we are focusing specifically on qualitative analysis of effective and ineffective school practices. Thematic analysis uncovered six themes highlighting effective and engaging practices such as additional educational support, video conferencing, and the use of learning management systems (LMS). Conversely, eight themes identified disengaging factors, including traditional teaching methods, limited interaction, inadequate educational support, challenges with assessment monitoring, adherence to epidemiological measures, and insufficient individualization in regular classes. Despite these challenges, many students showed understanding towards teachers and did not express negative feelings regarding the lack of enrichment and support. Notably, students valued teachers' responsiveness when initiating contact. Younger students received familial support, whereas secondary school students developed enhanced self-regulation and adopted new learning strategies. The study concludes that gifted students were not sufficiently recognized as a vulnerable group during ERE, often needing to self-organize amidst the educational disruptions caused by the pandemic. Findings underscore the necessity of ongoing teacher education in implementing engaging teaching methods across all student groups and supporting gifted students in virtual, hybrid, and traditional learning settings.
Keywords: gifted students, emergency remote education (ERE), qualitative study, effective school practices, additional school support